'Things are not working now': poverty, food insecurity and perceptions of corruption in urban Malawi. Issue 4 (2nd October 2018) - Riley, Liam; Chilanga, Emmanuel
ABSTRACT: Malawi is one of the world's least urbanised countries, but its cities are growing rapidly and poverty in urban Malawi is becoming a prominent political issue. Food insecurity is a widespread manifestation of urban poverty in Africa, especially in informal settlements. This article is based on in-depth interviews with food insecure residents of Lilongwe's informal settlements who, when asked why they were food insecure, overwhelmingly pointed to the Cashgate corruption scandal as a cause. There have been many political corruption scandals in Malawi, but the Cashgate scandal, which was revealed in September 2013 and reverberated throughout the political culture, has been among the most prominent and consequential of these scandals. The article seeks to contribute to literature on the political dimensions of urban food security in Africa while also presenting a way of understanding corruption from the point of view of vulnerable people whose lives have been directly and indirectly affected.